Faktor Risiko Diabetes Melitus dan Prevalensi Penyakit Jantung Koroner di RSU UKI Tahun 2021-2023 - Desy Ria Simanjuntak; Reynard Alexander Nugroho (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Coronary heart disease (CHD) remains a major cause of death globally, with its prevalence increasing over time. Diabetes mellitus is recognized as a significant risk factor for CHD. This study aims to explore the relationship between diabetes mellitus and CHD among patients at UKI General Hospital (RSU UKI). Utilizing a cross-sectional, retrospective, and descriptive-analytic design, this research analyzed medical records of CHD patients from January 2021 to December 2023, processed using SPSS software. Results indicated that CHD was most prevalent among individuals aged 60–69, with a higher incidence in men. Unemployment was common among CHD patients, and most had an education level above high school. During the study period, 79 CHD cases were recorded, with 21 patients having a history of diabetes mellitus. Data showed a consistent increase in CHD cases over the three-year period. The study revealed that individuals with diabetes mellitus were 3.5 times more likely to develop CHD. However, despite this finding, the data from RSU UKI indicated a relatively weak association between diabetes mellitus and CHD. These findings suggest that while diabetes mellitus is a notable risk factor for CHD, additional research is necessary to identify other contributing factors in this population.